Penerapan Teori Condito Sine Qua Non dalam Prinsip Apologetika Kristen - John Abraham Christiaan; Didit Yuliantono Adi; Tri Hananto; Stefanus Dully; Jerimias Manuhutu (Sekolah Tinggi Teologi Anugrah Indonesia, 2023)
The idea of writing about this topic originated from observations on social media that several Christian apologists were entangled in the law due to alleged blasphemy cases and the spread of false information when defending the Christian faith. This study aims to find the rule of law's cause and effect in blasphemy, provide insight into the purpose of apologetics, and explain how apologetics does not violate legal or religious norms. The method used in thisresearch is a qualitative method that prioritizes literature studies, collects data through scientific journals, and shares news on social media. The findings suggest that apologetics is a way of defending the faith when it is attacked by others, and it is an obligation for Christians. Apologetics is gentle, non-arrogant, and biblical. The maximum criminal penalty for blasphemy cases is ten years, and there is no equal legal protection between religious minorities and majorities in the application of the